An Analysis of Public Programs Related to Women’s Entrepreneurship and Access to Labor Markets - Goksen, Fatos; Olcay, Ozlem Altan; Alniacik, Ayse; Deniz, G. Ceren (World Bank, Washington, DC, 2016)
In the recent years, economic performance in Turkey has been praised due to its sustainedgrowth trends, stability and capacity to weather the global financial crisis. However, a number of issues related to the labor market and unemployment trends continue to be the economic and political underbelly to these positive trends. The conspicuously low labor forceparticipation among women over the years deserves special attention among these problems. The objective of this report is to provide an institutional analysis of public policies and programstargeting women’s access to labor markets and entrepreneurial activities. The report seeks to provide a comprehensive inventory of public programs, targeting women’s employment and entrepreneurship and evaluate the strengths and weaknesses of these programs with respect to their sustainability, institutional commitment, and their ability to address barriers to women’s labor force participation. In Turkey, women’s participation in the labor force has historically been low. While 34 percentof the women were in the labor force in 1990, the rate declined to 26 percent over the courseof the following decade and recovered up to 29 percent by 2012. Cross-country comparisons show that women in Turkey participate in the labor force at a much smaller rate compared to countries in all income groups. This is the case even in comparison with the lower-middle income countries, where women’s labor participation rate is 40 percent. A final focus in this study has been on the initiatives that aim to encourage women’s entrepreneurship. Given that the percentages of women among entrepreneurs in Turkey are even lower than that of women in the labor force, if the barriers to women’s entrepreneurial activities are removed, it appears that there is substantial room for improvement. This report sets its goal as interrogating in a holistic manner, programs’ objectives, contents,and ability to address problems standing in the way of women’s labor force participation. The aim of the report is not to conduct an impact analysis of these public programs, but to provide an extensive inventory of institutions and the specific departments and the programs that are directly responsible to carry out the public policies on the issue of women’s employment and entrepreneurship. Programs evaluated in this report were chosen on the basis of their scope both in terms of their targets and funding schemes. Local programs with very narrow scopes were not taken into the inventory. Only the programs, which target to create new employment and entrepreneurship opportunities for women with a wide sphere of influence, were inc luded. The public programs covered in this report can be also assessed based on the sectors ofeconomic activity in which women’s employment and entrepreneurship is promoted: Our report shows that the programs carry the danger of repeating existing gendered divisions of labor and the ensuing capacity to access the labor market. For long-term positive results inchanging existing horizontal and vertical segregations in the market, there should be more focus on how to change gendered assumptions about divisions of labor within the programs’design.